Phytochemical Constituents and Biological Activities of the Unexplored Plant Rhinanthus angustifolius subsp. grandiflorus - ŞENKARDEŞ, İSMAİL (MDPI, 2021)
In the present study, a total of 12 extracts of Rhinanthus angustifolius subsp. grandiflorus, an understudied hemiparasitic species, were obtained using different extraction techniques, namely, homogenizer-assisted extraction (HAE), maceration (MAC), soxhlet (SOX), infusion, and solvents (ethyl acetate, methanol, ethanol, and water), and were evaluated for their in vitro antioxidant and enzyme-inhibiting properties. Additionally, untargeted profiling based on high-resolution mass spectrometry targeted different phytochemical classes, namely, polyphenols, terpenoids, and alkaloids. The highest total phenolic and flavonoid contents were detected using methanol as the extraction solvent. Multivariate statistics following the untargeted profiling revealed that the extraction solvent had a hierarchically higher impact than the extraction method when considering the recovery of bioactive compounds. The methanolic extracts displayed the highest radical-scavenging antioxidant capacity, as provided by CUPRAC and FRAP assays. On the other hand, the water extracts (MAC and HAE) and the infusion extract showed the highest activity as metal chelators (25.66-27.51 mg EDTAE/g). Similarly, the water extract obtained by HAE and the infusion extract revealed the highest phosphomolybdenum activity (3.92 & PLUSMN; 0.14 and 3.71 & PLUSMN; 0.01 mmol TE/g, respectively). The different extracts also exhibited different enzyme inhibition potentials. For instance, HAE and MAC ethanolic extracts inhibited only alpha-amylase (0.69 & PLUSMN; 0.01 and 0.70 & PLUSMN; 0.01 mmol ACAE/g), while all the other extracts showed a dual inhibition against both carbohydrate-hydrolyzing enzymes tested (i.e., alpha-amylase: 0.07-0.69 mmol ACAE/g; alpha-glucosidase: 0.03-1.30 mmol ACAE/g). Nevertheless, the other extracts inhibited acetyl-, butyryl-cholinesterases, or both; MAC-water extract displayed no inhibition against the enzymes. Additionally, all the studied extracts were found to inhibit tyrosinase, ranging from 10.62 to 52.80 mg KAE/g. In general, the water extracts showed weaker inhibition towards the enzymes than the other extracts. This study demonstrated that R. angustifolius is an excellent source of natural antioxidants and enzyme inhibitors that could be further investigated and exploited for pharmaceutical purposes.
Keywords: Rhinanthus angustifolius; solvent extraction; phenolics/flavonoids; antioxidants; enzyme inhibitors; UHPLC-QTOF-MS; metabolomics; TYROSINASE INHIBITORS; CHEMICAL-COMPOSITION; ANTIOXIDANT ACTIVITY; ALPHA-GLUCOSIDASE; IN-VITRO; EXTRACTION; CHEMISTRY; PHENOLICS; AMYLASE; SEEDS